MHD Double-Diffusive Natural Convection in a Closed Space Filled with Liquid Metal: Mesoscopic Analysis - Sathiyamoorthi, Arun; Anbalagan, Satheesh; Öztop, Hakan Fehmi; Abu-Hamdeh, Nidal H. (Shahid Chamran Univ Ahvaz, Iran, 2021)
In this paper, the lattice Boltzmann approach is carried out to study the double-diffusive natural convection in a space encapsulating liquid metal is presented. The Uniform magnetic field is applied horizontally at the square domain and an insulated rectangular block is kept stationary at the center of the cavity. The linear increment of temperature and concentration is used at the left wall and cold temperature is applied at the right wall. Horizontal walls are adiabatic conditions. Horizontal walls are adiabatic conditions. The numerical analysis is performed at the range of Rayleigh number (10(3) <= Ra <= 10(5)), Lewis number (2 <= Le <= 10), buoyancy ratio (-2 <= N <= 2), Hartmann number (0 <= Ha <= 50) with Prandtl number (Pr) = 0.054. Results show that the increase in Ra tends to maximize heat and mass transfer rate while increasing Ha, decreases the same. The rise in Le diminishes heat transfer marginally but increasing the mass transfer significantly. The effect of N differs with different operating conditions, in general, the rate of heat and mass transfer is found to decrease with a decrease of N value.
Keywords: Liquid metal; Double-diffusive; Magnetic field; LBM; STR-BGK; Adiabatic block